FGD on Optimizing Corn Chip Production: Implementation of Innovative Equipment Technology in Corn Chip SMEs 513 - Miswar Budi Mulya; Muhammadin Hamid; Nursal; Ahmad Zaharin Aris; Naufal Sahwa Nughoro; Shafa Masrya Ismaya; Salsabila; Naysa Amanda; Rendra Syahputra Tanjung (Talenta Publisher, 2026)
This Focus Group Discussion (FGD) aims to identify strategies for optimizing corn chips (emping jagung) production through the implementation of innovative equipment technology in Micro, Small, and Medium Enterprises (MSMEs) in Bekiung Village, Langkat Regency. Bekiung Village is known as an agricultural area with abundant corn production, where corn is processed into emping jagung as a local snack product. However, the processing activities are still conducted manually, which limits production capacity and efficiency and becomes an obstacle in supporting the agricultural sector that remains the main economic pillar of the village. Through the FGD involving community members, village authorities, and the Village-Owned Enterprise (BUMDes) Bangun Mandiri Bekiung, various issues related to production constraints and technology needs were discussed. As a result, the implementation of innovative equipment technology was introduced as a practical solution to improve the efficiency and quality of corn processing. The program includes socialization on the benefits of corn processing, training on transforming corn into economically valuable products, provision of appropriate technology equipment to assist production, as well as continuous mentoring and evaluation to maintain product quality and market competitiveness. The results of the FGD indicate an increase in community understanding of technology utilization, stronger collaboration between stakeholders, and the development of a sustainable production improvement strategy. Therefore, the integration of community participation through FGD and the application of innovative equipment technology represents an effective approach to enhance productivity, strengthen rural economic resilience, and support the sustainable development of MSMEs in Bekiung Village.